Rekonstruksi Pemikiran Imam Syamsuddin Al-Sarakhsi Tentang Aktivitas Media Sosial Perempuan Dalam Masa 'Iddah - Afiful Huda (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2026)
The rapid development of social media has transformed patterns of social interaction from physical public spaces to digital public spheres, creating new challenges for the implementation of Islamic law, particularly the concept of ihdād for women during the 'iddah period. Previous studies have primarily focused on determining the legal status of social media use but have not developed a conceptual framework capable of reconstructing the meaning of ihdād in response to the transformation of digital society. This study aims to reconstruct Imam Syamsuddin al-Sarakhsi's legal thought on ihdād and examine its relevance to women's social media activities during the 'iddah period. This research employs a normative legal research design using a library research approach, supported by conceptual, philosophical, and Islamic legal theory (uṣūl al-fiqh) approaches. The primary sources include the Qur'an, Hadith, Al-Mabsūṭ by Imam al-Sarakhsi, classical and contemporary Islamic legal literature, maqāṣid al-sharī'ah studies, and recent scholarship on social media and Islamic family law. Data were analyzed through qualitative content analysis by interpreting the objectives of Islamic law (maqāṣid al-sharī'ah) and al-Sarakhsi's legal reasoning methodology. The findings reveal that, according to al-Sarakhsi, the essence of ihdād is not merely the restriction of women's physical mobility but the protection of honor, respect for the marital bond, and the regulation of conduct that preserves the meaning of mourning. Based on these findings, this study proposes the concept of Digital Ihdād, which reconstructs ihdād by focusing on digital conduct rather than prohibiting the use of social media itself. Educational, professional, economic, and family-related online activities remain permissible, whereas activities involving digital tabarruj, self-promotion for public attention, and romantic interactions are considered inconsistent with the objectives of ihdād. This concept contributes theoretically to the development of contemporary Islamic family law by integrating classical Islamic legal thought with the realities of the digital era through the framework of maqāṣid al-sharī'ah.